Content Validity Analysis of AKM Reading Literacy Test Instruments on Acid–Base Theory and Equilibrium Using the Aiken’s V Method - Dian Pratiwi; Sudarmin; Sri Yamtinah (Jurnal Inovasi Pendidikan Kimia, 2025)
The quality of educational assessment plays a crucial role in measuring students’ competencies in the 21st century, particularly reading literacy as assessed through the Minimum Competency Assessment (AKM). This study aimed to analyze the content validity of an AKM reading literacy test instrument on acid–base theory and equilibrium using Aiken’s V method. The instrument was developed in accordance with the AKM framework, covering various item formats and cognitive levels, and consisted of 30 test items supported by six contextual reading passages. Content validity was evaluated through expert judgment involving nine validators, comprising five university lecturers and four senior high school chemistry teachers. The validators assessed each item based on six criteria: relevance to content, clarity of item formulation, functionality of answer options, alignment with AKM reading literacy components, appropriateness of completion time, and language accuracy. Quantitative data were analyzed using Aiken’s V formula, while qualitative feedback was used to refine the test items. The results showed that all 30 items obtained Aiken’s V values equal to or exceeding the critical value of 0.71, indicating acceptable content validity. One item demonstrated high validity, while the remaining items exhibited moderate validity. Expert feedback further contributed to improving clarity, contextual accuracy, and alignment with acid–base equilibrium concepts. Overall, the findings confirm that the developed instrument is content-valid and suitable for measuring students’ reading literacy in chemistry. Future research should focus on empirical validation to assess reliability and construct validity.